2021
DOI: 10.1002/acn3.51387
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of low‐grade tumor‐related epilepsy and its predictors for surgical outcome

Abstract: Objectives: Low-grade tumors are the most common neoplasms inducing focal epilepsy; however, the short-and medium-term efficacy of surgery in epilepsy patients with low-grade tumors remains underappreciated. This study aims to summarize the clinical characteristics of epilepsy patients with low-grade tumors and to identify factors associated with postsurgical seizure-free outcomes. Methods: We retrospectively reviewed consecutive patients with lowgrade tumors who underwent subsequent epilepsy surgery in our ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
(138 reference statements)
3
8
0
Order By: Relevance
“…Total tumor resection is a well-known predictor of favorable postoperative seizure outcomes in patients with DLGG-related epilepsy. 25 , 26 , 28 In accordance with these study results, we also found such associations in this study, despite the differences in the patient cohort. Patients with residual tumors after surgery tend to have unfavorable seizure outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Total tumor resection is a well-known predictor of favorable postoperative seizure outcomes in patients with DLGG-related epilepsy. 25 , 26 , 28 In accordance with these study results, we also found such associations in this study, despite the differences in the patient cohort. Patients with residual tumors after surgery tend to have unfavorable seizure outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Factors including the extent of resection, seizure duration, age at surgery, and tumor location have been reported as predictors of seizure outcomes in patients with DLGG-related epilepsy. [24][25][26][27] In the present study, only patients with frontal DLGG-related epilepsy were included, and we found that total tumor removal and older age at seizure onset were independent predictors of favorable seizure outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because only patients with complete tumor resection were included in our research. Complications following the operation happened in 10.17% of cases, and permanent neurological impairments occurred in 5.93% of patients, similar to previous studies on surgical treatment for DLGG 2,8 . Notably, in this case series, patients who experienced surgical complications were seizure‐free at the final follow‐up.…”
Section: Discussionsupporting
confidence: 86%
“…Resection surgery is presently considered the most effective treatment for seizure control in patients with DLGG‐related epilepsy 1,7 . The extent of tumor excision is one of the most important predictors of seizure control after operation and is partly attributed to the neurotransmitter released by the residual tumor 8–10 . Accordingly, maximal safe resection of tumors is recommended as the standard of care for DLGG‐related epilepsy 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation